Factors influencing the post-exercise hepcidin-25 response in elite athletes - Peeling, P.; McKay, A. K.; Pyne, D. B.; Guelfi, K. J.; McCormick, R. H.; Laarakkers, C. M.; Swinkels, D. W.; Garvican-Lewis, L. A.; Ross, M. l. R.; Sharma, A. P.; Leckey, J. J.; Burke, L. M. (European Journal of Applied Physiology, 2017)
Purpose: The extent to which hepcidin regulation after acute bouts of exercise is influenced by baseline (resting) concentrations of key iron parameters remains uncertain. This investigation explored the influence of selected iron parameters and 25-km race walk time on 3-h post-exercise hepcidin-25 levels in international-level race walkers. Methods: Twenty-four male race walkers completed a graded exercise test and a 25-km race-walk trial. Throughout the 25-km race-walk, venous blood samples were collected pre-exercise, immediately post-exercise, and at 3-h post-exercise. Blood was analysed for serum ferritin, serum iron, Interleukin-6 (IL-6), and hepcidin-25 concentration. Results: IL-6 and hepcidin-25 increased (7.6- and 7.5-fold, respectively) in response to the 25-km race-walk trial (both p < 0.01). Significant individual relationships were evident between 3-h post-exercise hepcidin-25, baseline serum ferritin and serum iron (r > 0.62; p < 0.05). Multiple regression analysis showed that these two iron parameters, in addition to post-exercise IL-6 concentration and 25-km race-walk time, accounted for ~77% of the variance in 3-h post-exercise hepcidin-25 (p < 0.01). A median split by the cohort`s baseline serum ferritin concentration (LOW: 58.0 vs. HIGH: 101.8 µg/L; p < 0.01) showed a significant between group difference in the 3-h post-exercise hepcidin-25 (LOW: 6.0 ± 3.6 vs. 11.3 ± 5.4 nM; p = 0.01), despite no differences in baseline serum iron, post-exercise IL-6, or 25-km race-walk time (all p > 0.05). Conclusion: Despite exercise activating numerous hepcidin regulators, baseline iron status appears to play a dominant role in the regulation of hepcidin-25 in elite-level athletes subsequent to endurance exercise.